Sustainable Management Of Communal Violent Conflicts And Peaceful Co-Existence In Central Cross River State, Nigeria - Eteng, Felix Onen; Agbor, Uno Ijim (Advances in Social Sciences Research Journal, 2018)
Communal conflicts in central Cross River State occur very frequently with attendant destruction of lives and property. At extreme cases, communities have been sacked with no hope of returning to start the process of rebuilding their ruins. Efforts put forward by the various governments along judicial and administrative panels of inquiry have merely been very temporary in dealing with the situations. The aim of this paper is to examine principally the profound cause(s) of the rampant communal conflict in central Cross River State, Nigeria and to suggest possible alternatives to reducing tension and bring about peaceful coexistence among warring communities in this area. The paper got data from the exploration of varied literature and participant observer narrations. The paper reveals that land is the principal factor in the escalation of communal conflict in central cross river state. The paper attributes this to the excessive dependence on land for economic survival. As a strategy for reducing violent communal conflict in this zone, the paper recommends among others, a diversification of the rural economy through engaging the youth in skill development programmes that would open a new window for survival and reduce their concentration and pressure on land for survival.